Effect of different parameters utilized for image guided endodontic root canal preparation on temperature changes: an in vitro study - Zsolt Rajnics; Iván Mandel; Ákos Nagy; Kinga Turzó; Attila Mühl; Gyula Marada (BMC, 2024)
Abstract Background Navigated endodontics is a cutting-edge technology becoming increasingly more accessible for dental practitioners. Therefore, it is necessary to clarify the ideal technical parameters of this procedure to prevent collateral damage of the surrounding tissues. There is a limited number of studies available in published scientific literature referencing the possible collateral thermal damage due to high-speed rotary instruments used in guided endodontic drilling. The aim of our study was to investigate the different drilling parameters and their effect upon the temperature elevations measured on the outer surface of teeth during guided endodontic drilling. Methods In our in vitro study, 72 teeth with presumably narrow root canals were prepared using a guided endodontic approach through a 3D-printed guide. Teeth were randomly allocated into six different test groups consisting of 12 teeth each, of which, four parameters affecting temperature change were investigated: (a) access cavity preparation prior to endodontic drilling, (b) drill speed, (c) cooling, and (d) cooling fluid temperature. Temperature changes were recorded using a contact thermocouple electrode connected to a digital thermometer. Results The highest temperature elevations (14.62 °C ± 0.60 at 800 rpm and 13.76 °C ± 1.24 at 1000 rpm) were recorded in the groups in which drilling was performed without prior access cavity preparation nor without a significant difference between the different drill speeds (p = 0.243). Access cavity preparation significantly decreased temperature elevations (p < 0.01) while drilling at 800 rpm (8.90 °C ± 0.50) produced significantly less heating of the root surface (p < 0.05) than drilling at 1000 rpm (10.09 °C ± 1.32). Cooling significantly decreased (p < 0.01) temperature elevations at a drill speed of 1000 rpm, and cooling liquid temperatures of 4-6 °C proved significantly (p < 0.01) more beneficial in decreasing temperature elevations (1.60 °C ± 1.17) than when compared with room temperature (21 °C) liquids (4.01 °C ± 0.22). Conclusions Based on the results of our study, guided endodontic drilling at drill speeds not exceeding 1000 rpm following access cavity preparation, with constant cooling using a fluid cooler than room temperature, provides the best results in avoiding collateral thermal damage during navigated endodontic drilling of root canals.